2005
DOI: 10.1124/mol.105.013300
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of the G-Quadruplex-Stabilizing Telomerase Inhibitor 3,11-Difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium methosulfate (RHPS4) in Vitro: Activity in Human Tumor Cells Correlates with Telomere Length and Can Be Enhanced, or Antagonized, with Cytotoxic Agents

Abstract: Telomeric integrity is required to maintain the replicative ability of cancer cells and is a target for the G-quadruplex-stabilizing drug 3,11-difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium methosulfate (RHPS4). We report a senescent-like growth arrest in MCF-7 breast cancer cells, within 14 to 17 days, and a reduction in telomere length (from 5.2 kilobases (kb) to 4.7 and 4.3 kb after 17 days of treatment at 0.5 and 1 M, respectively). These effects occurred at noncytotoxic drug concentrations (doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 38 publications
(46 reference statements)
3
54
1
Order By: Relevance
“…First, mutant (dominant negative) hTERT-expressing cancer cells show reduced telomerase activity (inhibition), reduction in telomere length, chromosome fusions, slowing and eventual arrest of cell growth related to initial telomere length, and reduced tumourigenicity in immunodeficient nude mice (Hahn et al, 1999). Our own mutant-hTERT MCF-7 breast cancer cell line model also demonstrated markedly reduced clonogenicity and tumourigenicity (Cookson et al, 2005; data not shown). Second, GRN163L, a modified antisense oligonucleotide directed against the telomerase RNA component and the first telomerase inhibitor to enter clinical trials, produces in vitro telomerase inhibition, progressive telomere shortening, reduced clonogenicity and tumourigenicity of breast cancer cell lines, and suppression of tumour growth and lung metastases in animal models in vivo (Dikmen et al, 2005;Kelland, 2005;Hochreiter et al, 2006;Burger, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, mutant (dominant negative) hTERT-expressing cancer cells show reduced telomerase activity (inhibition), reduction in telomere length, chromosome fusions, slowing and eventual arrest of cell growth related to initial telomere length, and reduced tumourigenicity in immunodeficient nude mice (Hahn et al, 1999). Our own mutant-hTERT MCF-7 breast cancer cell line model also demonstrated markedly reduced clonogenicity and tumourigenicity (Cookson et al, 2005; data not shown). Second, GRN163L, a modified antisense oligonucleotide directed against the telomerase RNA component and the first telomerase inhibitor to enter clinical trials, produces in vitro telomerase inhibition, progressive telomere shortening, reduced clonogenicity and tumourigenicity of breast cancer cell lines, and suppression of tumour growth and lung metastases in animal models in vivo (Dikmen et al, 2005;Kelland, 2005;Hochreiter et al, 2006;Burger, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the in vitro data demonstrated that RHPS4 can act synergistically with Taxol in the UXF1138L cell line (Figure 5), as well as in MCF-7 cells, DNA-cross linking and alkylating agents such as cisplatin and temozolomide were antagonistic, possibly because these agents preferentially react at G-rich DNA sequences. Synergism between RHPS4 and other drugs were observed if there was an overlap between the molecular mechanism of the combination partners (Cookson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations